Biological effects of a zinc-substituted borosilicate bioactive glass on human bone marrow derived stromal cells in vitro and in a critical-size femoral defect model in rats in vivo - Saur, Merve; Kunisch, Elke; Fiehn, Linn Anna; Arango-Ospina, M.; Merle, Christian; Hagmann, Sébastien; Moghaddam-Alvandi, Arash; Stiller, A.; Hupa, L.; Renkawitz, Tobias; Kaňková, H.; Galusková, D.; et al. (Biomaterials science, 2024)
The borosilicate 0106-B1-bioactive glass (BG) composition (in wt%: 37.5 SiO2, 22.6 CaO, 5.9 Na2O, 4.0P2O5, 12.0 K2O, 5.5 MgO, 12.5 B2O3) has shown favorable processing characteristics and bone regeneration ability. This study investigated the addition of zinc (Zn) to 0106-B1-BG as an approach to improve this BG's biological properties. Different proportions of ZnO were substituted for CaO in 0106-B1-BG, resulting in three new BG-compositions: 1-Zn-BG, 2-Zn-BG, 3-Zn-BG (in wt%: 37.5 SiO2, 21.6/20.1/17.6 CaO, 4.0 P2O5, 5.9 Na2O, 12.0 K2O, 5.5 MgO, 12.5 B2O3 and 1.0/2.5/5.0 ZnO). Effects of the BG compositions on cytocompatibility, osteogenic differentiation, extracellular matrix deposition, and angiogenic response of human bone marrow-derived mesenchymal stromal cells (BMSCs) were evaluated in vitro. Angiogenic effects were assessed using a tube formation assay containing human umbilical vein endothelial cells. The in vivo osteogenic and angiogenic potentials of 3-Zn-BG were investigated in comparison to the Zn-free 0106-B1-BG in a rodent critical-size femoral defect model. The osteogenic differentiation of BMSCs improved in the presence of Zn. 3-Zn-BG showed enhanced angiogenic potential, as confirmed by the tube formation assay. While Zn-doped BGs showed clearly superior biological properties in vitro, 3-Zn-BG and 0106-B1-BG equally promoted the formation of new bone in vivo; however, 3-Zn-BG reduced osteoclastic cells and vascular structures in vivo. The acquired data suggests that the differences regarding the in vivo and in vitro results may be due to modulation of inflammatory responses by Zn, as described in the literature. The inflammatory effect should be investigated further to promote clinical applications of Zn-doped BGs.
Online veröffentlicht am 13. August 2024
Gesehen am 17.03.2025